2020
DOI: 10.1080/20473869.2020.1803025
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ strategies for home educating their children with Autism Spectrum Disorder during the COVID-19 period in Zimbabwe

Abstract: This study explored parents' strategies for home educating their children with Autism Spectrum Disorder (ASD) during the COVID-19 period in Harare Urban District in Zimbabwe. Embedded within international research findings on the subject, this qualitative study drew on a purposive sample of eight parents. Telephonic individual interviews, information sheets, and field notes were used to collect data. A constant comparative approach of data organization with continuous adjustment was used throughout the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 9 publications
3
47
1
7
Order By: Relevance
“…Families emphasized that their children were happier and stress was reduced due to the counseling support. This result also supports the results of research conducted in the literature (MAJOKO & DUDU, 2020;CAHAPAY, 2020;NARZISI, 2020). Majoko & Dudu (2020) stated in their study that the complementary roles of parents and all family members in homeschooling children with ASD during the period when they had to stay at home due to the pandemic facilitated the transition of these children from school to routine activities at home.…”
Section: Table 1 the Difficulties Of Families In The Distance Education Process And Solutionssupporting
confidence: 87%
See 1 more Smart Citation
“…Families emphasized that their children were happier and stress was reduced due to the counseling support. This result also supports the results of research conducted in the literature (MAJOKO & DUDU, 2020;CAHAPAY, 2020;NARZISI, 2020). Majoko & Dudu (2020) stated in their study that the complementary roles of parents and all family members in homeschooling children with ASD during the period when they had to stay at home due to the pandemic facilitated the transition of these children from school to routine activities at home.…”
Section: Table 1 the Difficulties Of Families In The Distance Education Process And Solutionssupporting
confidence: 87%
“…This result also supports the results of research conducted in the literature (MAJOKO & DUDU, 2020;CAHAPAY, 2020;NARZISI, 2020). Majoko & Dudu (2020) stated in their study that the complementary roles of parents and all family members in homeschooling children with ASD during the period when they had to stay at home due to the pandemic facilitated the transition of these children from school to routine activities at home. The researchers also stated that the fact that parents interacted online, both among themselves and with their children's teachers and therapists, and received support from them helped children to develop an awareness of this COVID-19 period and relevant safety measures.…”
Section: Table 1 the Difficulties Of Families In The Distance Education Process And Solutionssupporting
confidence: 87%
“…Hampir seluruh sistem pendidikan tutup sementara karena pandemi COVID-19 (Cahapay, 2020 ;Majoko & Dudu, 2020). Keputusan pemerintah untuk menutup lembaga sekolah secara serentak berdampak pada perubahan sistem pembelajaran di sekolah secara cepat dan ini membuat kesulitan bagi banyak pihak sekolah, orang tua dan juga anak.…”
Section: Pendahuluanunclassified
“…numbers As examples, initial quantitative evidence related to autism has quickly become available from China [4] , Italy [5] , the UK [6] , the USA [7] , Australia [8] , Saudi Arabia [9] , Iran [10] , or Japan [11] , and further qualitative research was reported from the Philippines [12] , Zimbabwe [13] , or Peru [14] . Topics were diverse.…”
Section: Regional and Temporal Factorsmentioning
confidence: 99%